APLIKASI PUPUK ORGANIK BERBASIS MIKORIZA UNTUK MENINGKATKAN HASIL KEDELAI DI DAERAH SEMI ARID TROPIS LOMBOK UTARA - W. Astiko; I. R. Sastrahidayat; S. Djauhari; A. Muhibuddin (Universitas Tribhuwana Tunggadewi, 2012)
A pot trial using sandy soil samples from the dryland farming system of Northern Lombok was conducted in the Faculty of Agriculture, Mataram University to study the role of indigenous of mycorrhiza to improve soil fertility, nutrients uptake, soybean growth and yields. Treatments tested were: without mycorrhiza inoculation with no fertilizers as control (Ko), inoculation of mycorrhiza with no fertilizers (K1), inoculation of mycorrhiza with cattle manure (K2), inoculation of mycorrhiza plus rock phosphate (K3) and inoculation of mycorrhiza plus inorganic fertilizers (K4). The five treatments were arranged in a Completely Randomized Block Design with four replicates. Soil fertility status observed were concentrations of N, P, K, and organic-C and soil pH. Agronomic measurements were crop nutrients uptake (N, P, K and Ca), growth and yield. Variables dealing with mycorrhiza were recorded for: total population of mycorrhiza and percentage of roots infection. Overall, the results of study showed that soil fertility status as well as performance of growth and yield of soybean tended to be higher in arbuscular mycorrhiza (AM) inoculated soils compared to other treatments. Therefore, the application of AM along with application of cattle manure would be promising to sustain soil productivity under soybean cropping system